2017
DOI: 10.4103/ayu.ayu_209_15
|View full text |Cite
|
Sign up to set email alerts
|

A simple dietary addition of fenugreek seed leads to the reduction in blood glucose levels: A parallel group, randomized single-blind trial

Abstract: Introduction:Diabetes is prevalent in India. This study was conducted to assess the impact of ingestion of fenugreek seed on fasting blood glucose levels and glycosylated hemoglobin (HbA1C) levels in patients of Type 2 diabetes mellitus controlled with diet, exercise and oral hypoglycemic agents (OHAs) or insulin.Aims:Assessment of impact of ingestion of Trigonella foenum-graecum or fenugreek seed in patients with Type 2 diabetes controlled with OHAs and insulin on fasting blood sugar levels and HbA1C levels.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 12 publications
1
22
0
2
Order By: Relevance
“…31 Another clinical trial proved that fenugreek seeds water significantly reduced FBS and HbA 1 c within 6 months. 32 A 10 days RCT of stress induced hyperglycemia (SIH) in critically ill patient used 3 gm of fenugreek seeds powder by gavage twice a day along with routine medication found significant reduction in mean blood glucose levels and good prognosis observed than the control group with routine medication. 33 Another 3 month RCT found a significant reduction in FBS and lipid profile after intake of 2 gm fenugreek (capsule form three times per day along with metformin) than 5 gm glibenclamide (once a day along with metformin) among uncontrolled type 2 DM.…”
Section: Discussionmentioning
confidence: 99%
“…31 Another clinical trial proved that fenugreek seeds water significantly reduced FBS and HbA 1 c within 6 months. 32 A 10 days RCT of stress induced hyperglycemia (SIH) in critically ill patient used 3 gm of fenugreek seeds powder by gavage twice a day along with routine medication found significant reduction in mean blood glucose levels and good prognosis observed than the control group with routine medication. 33 Another 3 month RCT found a significant reduction in FBS and lipid profile after intake of 2 gm fenugreek (capsule form three times per day along with metformin) than 5 gm glibenclamide (once a day along with metformin) among uncontrolled type 2 DM.…”
Section: Discussionmentioning
confidence: 99%
“…Fenugreek seeds have a synergistic effect on diet control exercise and fasting blood glucose and HbA1c [40].…”
Section: Anti-inflammatory and Anti-arthritic Activity Of Fenugreek Seedsmentioning
confidence: 99%
“…An independent meta-analysis of 12 randomized clinical trials reported that fenugreek significantly decreased the levels of fasting blood glucose, 2-h postprandial blood glucose, hemoglobin A1c, and total cholesterol (Gong et al, 2016). Furthermore, several other studies have shown the promising effects of fenugreek in lowering hemoglobin A1c levels (Ranade & Mudgalkar, 2017;Suchitra & Parthasarathy, 2015) and improving insulin sensitivity (Kiss et al, 2018;Sharma & Raghuram, 1990;Suchitra & Parthasarathy, 2015). In a study with 114 T2DM patients (Geberemeskel, Debebe, & Nguse, 2019), a fenugreek powder solution, orally consumed for 30 consecutive days, was able to significantly improve the lipid profile of these patients compared with a placebo control.…”
Section: Crop Sciencementioning
confidence: 99%